SiRNA suppression of hTERT using activatable cell-penetrating peptides in hepatoma cells. Issue 2 (18th March 2015) - Li, Hua; He, Jiwen; Yi, Huimin; Xiang, Guoan; Chen, Kaiyun; Fu, Binsheng; Yang, Yang; Chen, Guihua
Abstract : In the present study, we delivered human telomerase reverse transcriptase (hTERT) siRNA into SMMC-7721 hepatoma cells using a matrix metalloproteinase-2 (MMP2)-activatable cell-penetrating peptide (aCPP). The siRNA subsequently induced down-regulation of the hTERT gene and G1 -arrest, implicating the utility of this delivery system in cancer therapy. Abstract : Activatable cell-penetrating peptides (aCPPs) allow non-viral, low cytotoxic and selective delivery of compounds into target cells for cancer therapy. In tumour cells, up-regulation of human telomerase reverse transcriptase (hTERT) frequently occurs and is being considered as a target in cancer diagnosis and treatment. siRNA sequence that target hTERT mRNA can silence the gene and reduce hTERT protein expression to reduce cell proliferation and inhibit cell growth. In our study, we tested a matrix metalloproteinase-2 (MPP2) aCPP in delivering hTERT siRNA into hepatocellular carcinoma cells (SMMC-7721) to silence the hTERT gene. Cultured SMMC-7721 cells were transfected with a complex of aCPPs and hTERT-specific siRNA-encoding or control plasmids. Compared with cells treated with the complex of control plasmid–CPPs, cells treated with the hTERT-specific siRNA-encoding plasmid–CPP complex had a prolonged G1 -phase, but a shorter G2 /S-phase, indicating a G1 -arrest. Treatment with the hTERT-specific siRNA resulted in a significant decrease (by 26%; P <0.05) in hTERT mRNA levels. The aCPPs tested in this study provides a non-viral delivery of siRNA into cancer cells to silence target genes in cancer therapy.